2017 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--27661
|View full text |Cite
|
Sign up to set email alerts
|

Blowing off Steam Tables

Abstract: is an associate professor in Mechanical Engineering at Rowan University. He received his Ph.D. from University of Michigan in 2008 and his B.S. from Union College in 2003. His research interests include combustion synthesis of nanoparticles and combustion catalysis using nanoparticles. He is also involved in developing educational apps for instructional and research purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…To counter that we must recognize the FE exam already relies exclusively on the pressure-enthalpy (P-h) property chart for refrigerant R-134a to solve refrigeration problems; at the same time supplying the tables to solve steam problems. Our own research has shown that students using water property charts are able to internalize property trends (Bakrania and Carrig, 2016), predict changes in properties (Bakrania and Mallouk, 2017), and perform better on engineering problems involving steam as a working fluid (Bakrania and Haas, 2019). This body of evidence must be translated into engineering education practice that is easy to adopt and fit the existing instructional content.…”
Section: Advances In Engineering Educationmentioning
confidence: 99%
“…To counter that we must recognize the FE exam already relies exclusively on the pressure-enthalpy (P-h) property chart for refrigerant R-134a to solve refrigeration problems; at the same time supplying the tables to solve steam problems. Our own research has shown that students using water property charts are able to internalize property trends (Bakrania and Carrig, 2016), predict changes in properties (Bakrania and Mallouk, 2017), and perform better on engineering problems involving steam as a working fluid (Bakrania and Haas, 2019). This body of evidence must be translated into engineering education practice that is easy to adopt and fit the existing instructional content.…”
Section: Advances In Engineering Educationmentioning
confidence: 99%
“…Additionally, charts reinforce the interdependent nature of the state properties and help the students develop a mental model of equation of state for water. Previous studies have already demonstrated that the students who use water property charts are better at predicting state property trends when going from one state to the other [7,8]. Online/web tools or the steam tables, on the other hand, often deliver only point values without contextual information related to the fluid region.…”
Section: Charts Vs the Rest (Online/web Tools Or Steam Tables)mentioning
confidence: 99%
“…To encourage students to embrace the property charts and familiarize them with the overall concept, custom designed T-shirts with printed T-s charts were distributed. Students continue to wear these T-shirts beyond the course completion, often inspiring discussions with other colleagues on what the chart represents [8]. An iPad app, titled Clausius , was designed to demonstrate the dynamic changes in properties as one glides their fingers across a T-s chart [19].…”
Section: Transitioning To Property Chartsmentioning
confidence: 99%
See 2 more Smart Citations